1985
DOI: 10.1002/cne.902390408
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic neurons containing CCK‐8‐like and/or VIP‐like immunoreactivities in the rat hippocampus and dentate gyrus

Abstract: The coexistence of cholecystokinin-octapeptide-like (CCK-L) and/or vasoactive-intestinal-polypeptide-like immunoreactive (VIP-LI) materials and glutamate decarboxylase (GAD) was studied in the rat hippocampus and dentate gyrus by means of immunohistochemistry. Consecutive 40-micron-thick sections were incubated in different antisera and those cells which were bisected by the plane of sectioning so as to be included at the paired surfaces of two adjacent sections were identified. The coexistence of the immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(133 citation statements)
references
References 21 publications
14
119
0
Order By: Relevance
“…The morphological features of neurons with GABA-LI were similar to those reported previously in the hippocampus using GABA or GAD antibodies in the rat (Frotscher et al, 1984;Kosaka et al, 1984;Frotscher and Zimmer, 1987;Leranth and Frotscher, 1987a, b) and human (Schlander et al, 1987). It is interesting that the ultrastructural characteristics of GABAergic neurons did not differ significantly between the hippocampus and DG since GABAergic perikarya have been divided into several subclasses based on light microscopic distribution and morphological characteristics (Seress and Ribak, 1983) and colocalization with other neurotransmitters (Somogyi et al, 1984;Kosaka et al, 1985;Kunkel and Schwartzkroin, 1988) or proteins (Kosaka et al, 1987a).…”
Section: Th As An Indicator Of Catecholaminessupporting
confidence: 83%
See 1 more Smart Citation
“…The morphological features of neurons with GABA-LI were similar to those reported previously in the hippocampus using GABA or GAD antibodies in the rat (Frotscher et al, 1984;Kosaka et al, 1984;Frotscher and Zimmer, 1987;Leranth and Frotscher, 1987a, b) and human (Schlander et al, 1987). It is interesting that the ultrastructural characteristics of GABAergic neurons did not differ significantly between the hippocampus and DG since GABAergic perikarya have been divided into several subclasses based on light microscopic distribution and morphological characteristics (Seress and Ribak, 1983) and colocalization with other neurotransmitters (Somogyi et al, 1984;Kosaka et al, 1985;Kunkel and Schwartzkroin, 1988) or proteins (Kosaka et al, 1987a).…”
Section: Th As An Indicator Of Catecholaminessupporting
confidence: 83%
“…The presence of dcvs amidst unlabeled smaller vesicles raises the prospect that GABA may be colocalized in these terminals with other transmitters. Cholecystokinin, vasoactive intestinal peptide, and somatostatin are possible candidates since these substances coexist within GABAergic neurons in the hippocampal formation (Somogyi et al, 1984;Kosaka et al, 1985;Kunkel and Schwartzkroin, 1988).…”
Section: Th As An Indicator Of Catecholaminesmentioning
confidence: 99%
“…Functionally, they are assumed to mediate both feedforward and feedback inhibition of pyramidal cells (Lacaille et al, 1987;Lacaille and Schwarzkroin, 1988;Samulack et al, 1993). Interneurons located in the distal radiatum that f ulfill the criterion to receive RE input are likely the ones containing GABA as well as the putative excitatory transmitters cholecystokinin (CCK) and /or vasoactive intestinal polypeptide (V I P) (Kosaka et al, 1985;Gulyás et al, 1991;Haas and Gáhwiler, 1992;Acsády et al, 1996a,b). GABA-CCK cells have been observed to form symmetrical synapses with pyramidal cell bodies (Harris et al, 1985;Nunzi et al, 1985); GABA-V I P cells have been shown to contact primarily other interneurons (Acsády et al, 1996a,b;Freund and Buzsáki, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…20,22 Adjacent sections were reacted for CB1 and for one of the other antigens, and bisected cell bodies were identified on the common surfaces of both sections using capillaries as landmarks using a ×100 oil immersion objective. Cells were only included in the analysis if both matching halves could be unequivocally identified (whether negative or positive).…”
Section: Methodsmentioning
confidence: 99%